(3eYGfi GdbQBfs - (3jMji Hf RjGO Hf YHO Gddg Hf efXhQ GdOjdeqj, ehdi Hfj CSO (B((3Ch Hfj efbQ(B) (3CHhRcQjGA, GdeYQha HGdaQGA,J (B207 (3g` s
(3ChdgG (B:s
(3MOKfG CHh efUhQ fUQ ehdi CMeO Hf QSJg bGd MOKfG gPG cJGH ajg eYGfi GdbQBf , CedGg YdjfG CHh RcQjG jMji Hf RjGO GdaQGA s
(3BNQgG (B:s
(3ef JaSjQ ShQI GdfGS (B: (3bGd (B" (3hCfg cGf QLGd ef GdEfS jYhPhf HQLGd ef GdLf (B" (3aSei GdQLGd ef GdLf hGdEfS hGddg CYde s
(3Hg fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B145 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B198s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs